ANALISIS PRODUKSI, KURS, HARGA TERHADAP EKSPOR MINYAK KELAPA SAWIT DAN PDB DI INDONESIA TAHUN 2013-2016 - Nyoman Djinar Setiawina, Yohana Yeria Aruan, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 12 (2019): Vol. 8, No.12, Desember 2019, pp (2807-3114), 2019)
Indonesia is the number one largest country in the world for exporting palm oil, export production and volume always increases every year followed by land area and increases state income. The research objective was to determine the effect of Crude Palm Oils production, the rupiah exchange rate, the international price of Crude Palm Oils, on Crude Palm Oil exports and Indonesia's GDP in 2013-2016. The type of data used is sekundr data with a time series (Times Series) from 2013-2016 with the path analysis method (Path Analysis). In the general period of 2013-016 the results of this study showed that palm oil production, the exchange rate of the rupiah against the dollar had a positive and significant influence on the export volume of palm oil and Indonesia's GDP in 2013-2016, the price of international palm oil had a negative influence and significant volume of exports of palm oil and Indonesia's GDP in 2013-2016, and palm oil production, the exchange rate of the rupiah against the dollar, and the price of international palm oil have an influence and significant impact on Indonesia's GDP through the volume of palm oil exports in 2013 -2016.